Pengaruh Nilai Taksir dan Peran Media Sosial terhadap Keputusan Nasabah Menggadai Barang Emas pada Pegadaian Prailiu - Ina, Sisilia; Situmorang, Tumpal Pangihutan (LPPM Institut Pendidikan Nusantara Global, 2024)
The purpose of this study is to explore the influence of appraisal value and the role of social media on consumer decisions in pawning gold goods. This research method also uses non-probability sampling with proposive sampling techniques. The sampling criteria are to pawn gold at the Prailiu branch pawnshop at least 2 or more times and be domiciled in Waingapu. Data analysis using multiple regression, the results showed that the value of estimates and promotions had a significant effect on the decision to pawn gold. This type of research uses a quantitative approach. The population in this study amounted to 80 respondents and this study was conducted by distributing questionnaires directly.